HORMONE-DEPENDENT GYNECOLOGICAL DISEASES IN INFERTILE WOMEN FROM MAIN ETHNIC GROUPS OF BURYAT REPUBLIC - T. B. Tsyrenov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article presents the results of examination of 156 women from infertile couples (88 Russians, 68 Buryats). The uterine factor of infertility was observed more often in Buryats due to higher rate of uterine fibroids in Buryat women with secondary infertility in comparison with Russian infertile women: 69,7 % and 21,8 %, respectively. No significant difference was shown in adenomyosis and endometrium hyperplasia frequency.